The evidence supporting methods of tooth width measurement: Part II. Digital models and intra-oral scanners - Naidu Devan; Freer Terrence J. (Sciendo, 2013)
Digital models and intra-oral scanners are gaining increasing popularity in orthodontic diagnosis and treatment planning by allowing clinicians to store and 'virtually' analyse dental casts. The present paper reviews the various digital model programs and available intra-oral scanners and presents the research which has tested their accuracy. With this information, clinicians may be better informed to adopt the most appropriate system.